2009
DOI: 10.1093/pcp/pcp044
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Defense Responses in Arabidopsis Induced by the Cell Wall Protein Fractions from Pythium oligandrum Require SGT1, RAR1, NPR1 and JAR1

Abstract: The cell wall protein fraction (CWP) is purified from the non-pathogenic biocontrol agent Pythium oligandrum and is composed of two glycoproteins (POD-1 and POD-2), which are structurally similar to class III elicitins. In tomato plants treated with CWP, jasmonic acid (JA)- and ethylene (ET)-dependent signaling pathways are activated, and resistance to Ralstonia solanaceraum is enhanced. To dissect CWP-induced defense mechanisms, we investigated defense gene expression and resistance to bacterial pathogens in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 72 publications
3
27
0
3
Order By: Relevance
“…Because induced resistance to Ralstonia solanacearum is not compromised in CWP-treated nahG transgenic tomato mutants (transgenic plants expressing the bacterial salicylate hydroxylase gene) while it is compromised in jai1-1 mutants with an impaired JA signalling pathway (Hase et al, 2008), it is tempting to speculate that, analogous to other beneficial associations (Van der Ent et al, 2009), the JA-dependent signalling pathway is required in the CWP-mediated induced resistance. The recent use of an array of mutants with different impaired defence signalling pathways brought conclusive evidence for an involvement of the JA-and ETdependent signalling pathways in the CWP-induced plant response (Kawamura et al, 2009). It seems likely that the strong activation of the JA signalling pathway by CWPs from P. oligandrum results in the suppression of the SA signalling pathway through hormonal cross-talk mechanisms.…”
Section: Signalling Pathways Involved In P Oligandrummediated Inducementioning
confidence: 99%
“…Because induced resistance to Ralstonia solanacearum is not compromised in CWP-treated nahG transgenic tomato mutants (transgenic plants expressing the bacterial salicylate hydroxylase gene) while it is compromised in jai1-1 mutants with an impaired JA signalling pathway (Hase et al, 2008), it is tempting to speculate that, analogous to other beneficial associations (Van der Ent et al, 2009), the JA-dependent signalling pathway is required in the CWP-mediated induced resistance. The recent use of an array of mutants with different impaired defence signalling pathways brought conclusive evidence for an involvement of the JA-and ETdependent signalling pathways in the CWP-induced plant response (Kawamura et al, 2009). It seems likely that the strong activation of the JA signalling pathway by CWPs from P. oligandrum results in the suppression of the SA signalling pathway through hormonal cross-talk mechanisms.…”
Section: Signalling Pathways Involved In P Oligandrummediated Inducementioning
confidence: 99%
“…Indole acetic acid (IAA) is a growth hormone that has been correlated with JA activity (Kawamura et al, 2009). Local IAA accumulation in the basal meristem of Arabidopsis roots was shown to increase after JA treatment (Sun et al, 2009).…”
Section: Hormone Metabolismmentioning
confidence: 99%
“…1). Coronatine-regulated tyrosine aminotransferase (CORI3, spots 146 and 147) has been reported to be induced by JAs and aphid feeding (Myzus persicae and Brevicoryne brassicae) (Kusnierczyk et al, 2007;Kawamura et al, 2009). The up-regulation of these proteins indicates that JAs are potent regulators of the processes involved in abiotic and biotic stress response and tolerance (Desikan et al, 2001;Goulas et al, 2007;Jiang et al, 2007).…”
Section: Stress and Defense-related Proteinsmentioning
confidence: 99%
“…This biocontrol agent quickly and massively colonizes tomato root tissues like Pythium-major pathogens, but its colonization is associated with neither host wall disruption nor host cell alternations and is followed by induction of several host defense reactions (Le Floch et al, 2005). We previously reported that a cell wall protein fraction (CWP) of P. oligandrum containing two novel elicitin-like proteins, POD-1 and POD-2 induced defense reactions in sugar beet (Takenaka et al, 2003), wheat (Takenaka et al, 2003), tomato Kawamura et al, 2009a), and Arabidopsis thaliana (Kawamura et al, 2009b). In tomato leaves treated with CWP, JA-and ET-dependent signaling pathways are activated (Kawamura et al, 2009a).…”
mentioning
confidence: 99%